Atypical Presentation of Hypothyroidism Mimicking Rheumatism: A Case Report - Robab Aboutorabi; Reza Bustani; Motahareh Mirdoosti; Maral Barzegar-Amini (Patient Safety and Quality Improvement Journal)
Introduction: Hypothyroidism typically manifests as tiredness, somnolence, weight gain, cold intolerance, hair loss, menstrual abnormalities, and musculoskeletal symptoms. Non-specific musculoskeletal symptoms are common and impair the patient’s quality of life. Hypothyroid myopathy has been described as fatigue, myalgia, cramps, stiffness, myoedema, and weakness. Case Report: Here, we present a patient with muscular cramps and numbness of the toes, initially diagnosed with rheumatism. After a year of treatment with no positive results, the patient was diagnosed with hypothyroidism due to abnormal levels of thyroid hormone. Three months after treatment with levothyroxine, the patient experienced a complete resolution of symptoms. Conclusion: This particular case underscores the crucial need to consider hypothyroidism as a differential diagnosis in all patients with unexplained musculoskeletal symptoms. By doing so, we can avoid potential misdiagnoses and ensure timely and effective treatment.